Racial differences in associations between baseline patterns of radiographic osteoarthritis and multiple definitions of progression of hip osteoarthritis: the Johnston County Osteoarthritis Project. Issue 1 (December 2015) - Foley, Bridget; Cleveland, Rebecca; Renner, Jordan; Jordan, Joanne; Nelson, Amanda
Abstract Background To identify baseline radiographic features that predict hip osteoarthritis (HOA) progression, and to explore differences in these associations by race. Methods Radiographs from the community-based Johnston County OA Project were scored using Kellgren-Lawrence (KL) grade and for presence and location of joint space narrowing (JSN), osteophytes, and subchondral changes. Associations between these features and HOA progression (increase of at least 1 KL grade, interval hip replacement, range of motion [ROM, a reduction of ≥10° in internal rotation], or disability [increase of ≥0.2 in Health Assessment Questionnaire scores], or Any of these) were assessed using logistic regression, adjusting for age, gender, race, hip injury, BMI, education, smoking and follow-up time, accounting for multiple comparisons. Race interactions were assessed and analyses stratified as indicated. Results The sample (n = 1, 422) included 40 % men and 26 % African American (AA) participants, with mean age 61 years and BMI 29 kg/m2 . The baseline frequency of radiographic hip OA (RHOA) between Caucasians and AAs was similar (23 %), although some radiographic features differed. AAs were more likely to have progression defined by ROM or disability or Any progression; Caucasians were more likely to have RHOA progression. JSN, subchondral sclerosis, and medial osteophytes were associated with increased RHOA progression overall; JSN was associated with disability progression only in AAs, while lateral osteophytes were associated with ROM progression only in Caucasians. Conclusions AAs and Caucasians exhibited differences in the radiographic presentation and progression patterns of HOA, with AAs reporting progressive pain and disability, while Caucasians had more RHOA progression.